Documentary theatre as a means of cultivating and strengthening citizenship among adult students in the School of 18 Ano addiction rehabilitation unit - Dafni, Roumpini (Education & Theatre, 2024)
This article refers to an action research project investigating the impact of documentary theatre as a means of cultivating citizenship among the adult students of the School of 18 Ano, the Addiction Rehabilitation Unit of the Psychiatric Hospital of Attica. To this end, twelve interventions based on documentary theatre and educational drama techniques were designed and delivered to 11 students during the 2022–2023 school year. A mixed research approach was adopted to ensure a more comprehensive investigation of the research questions. The analysis of the quantitative data showed an improvement in the citizenship of the experimental group but no statistically significant differences before and after the interventions. On the contrary, the analysis of the qualitative data suggested an improvement in civic skills (collaboration and critical analysis), attitudes (participation and diversity) and interest and personal involvement. This improvement is indeed linked to the techniques of documentary theatre.